Dampak Kepadatan Penduduk terhadap Kesehatan Masyarakat & Lingkungan di Kecamatan Medan Tembung - Ghaly Fathur Rahman; Muhammad Ikhsan Fadhilah; Pramudya Gandara (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Population density plays a critical role in shaping public health outcomes and environmental quality, particularly in rapidly urbanizing regions. This study aims to analyze the relationship between high population density and its impacts on sanitation conditions, air quality, access to clean water, and the incidence of various diseases in densely populated areas. The research adopts a qualitative descriptive approach by combining a comprehensive literature review with field observations conducted in several urban areas characterized by high population concentration. The findings reveal that increased population density is closely associated with environmental degradation, including inadequate sanitation systems, reduced air quality due to pollution, and limited availability of clean water. These environmental challenges contribute directly to a higher prevalence of health problems, such as respiratory infections, waterborne diseases, and other communicable illnesses. Overcrowded living conditions also intensify the spread of diseases, placing additional pressure on public health infrastructure. Furthermore, the study highlights that insufficient public facilities and poor environmental management exacerbate the negative effects of population density on both health and the environment. To address these challenges, effective strategies are required, including population growth control, improved urban planning, and enhanced investment in public health and environmental sanitation facilities. Strengthening community awareness and participation in maintaining environmental cleanliness is also essential. Overall, this study emphasizes the need for integrated policies that balance population management with sustainable environmental and public health development.